Characteristics of 137 macaw palm (Acrocomia aculeata) fruit accessions from Goias, Brazil - Reis, Edésio Fialho dos; Pinto, Jefferson Fernando Naves; Assunção, Hildeu Ferreira da; Netto, Antonio Paulino da Costa; Pereira da Silva, Danielle Fabiola (Comunicata Scientiae, 2019)
Accessions of macaw palm fruits from the State of Goias, Brazil were characterized aiming the identification of groups with similar characteristics and indicate groups with higher agronomic potential, using multivariate tools. Fruit were harvested with completed yellow fruit bunches without whitish scores. The evaluated variables were fruit and almond length, fruit and almond diameters, fruit and dehydrated almond weight, average number of almonds, oil percentage of almond and dried fruit. The genetic diversity of populations was evaluated by Ward’s clustering method and Person´s correlation was obtained to evaluate the relative importance of each characteristic and variance analysis associated with Tukey´s test to verify the group’s effects. The studied population demonstrated great variability. The characteristics that most contributed to the variability were fruit weight and diameter and the almond´s oil percentage. Ward´s group analysis revealed six groups of similarity, being significant for all evaluated characteristics. Group VI stood out for all evaluated characteristics and group III presented the best averages for the almond´s weight and almonds and dried fruit oil percentage.